TRANSCULTURAL DISCOURSE – A NOT CONCLUDE CROSSING – - Ana Lúcia Branco (Travessias, 2007)
The first part of this work is to introduce the methodology aspect that shows the ngel Ramas approach a Latin American as a project to be described by the intellectual work trough the meaning of the transculturation, understanding it as a process of lost, selections, rediscovers and incorporations between two cultures that enter in a contact. The second part is use it in Grande serto: veredas, specificationly, in the moment of the open trial of the character Z Bebelo when Riobaldo, by the language, itself shows